The Feasibility Content and Presentation of Competent Indonesian Language Textbooks for SMA/Ma Grade XI Merdeka Curriculum Published by Erlangga - Damayanti, Elisa Dyah Kusuma; Sulistyaningrum, Septina (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2024)
Textbooks are one of the most widely used learning resources to improve student quality. The selection of textbooks is adjusted to the learning materials and current curriculum, as known as the Merdeka Curriculum. This research aims to analyze the appropriateness of the content and presentation of Competent Indonesia Language textbooks for class XI SMA/MA curriculum published by Erlangga. This research includes qualitative descriptive research. The focus of this research is in accordance with the BSNP assessment standards regarding the appropriateness of the content and presentation of textbooks. The variables of this research are all chapters in the Competent Indonesia Language textbooks for class XI SMA/MA published by Erlangga. The data sources used in this research consist of primary data and secondary data. The primary data source in this research is the Competent Indonesia Language textbooks for class XI SMA/MA class IX published by Erlangga. Secondary data sources in this research are relevant interviews, articles, and books. The data collection techniques are use note-taking and documentation techniques. Data analysis techniques are use interactive models. The validity test of the data using triangulations sources and theory. The results of the research show that the appropriateness of the Competent Indonesia Language textbooks for class XI SMA/MA the Merdeka Curriculum published by Erlangga includes the suitability of the material with the Learning Outcomes in the Merdeka Curriculum which consists of completeness, breadth and depth of the material, obtaining a percentage of 63.5% (feasible) while the assessment of the accuracy of the material obtained a percentage of 76.25% (feasible). The feasible of presentation in the Competent Indonesia Language textbooks for class XI SMA/MA Merdeka Curriculum published by Erlangga as a whole includes presentation techniques getting a percentage of 75.00% (feasible) while learning presentations get a percentage of 75.00% (feasible), as well as completeness of presentation obtained a percentage of 75.00% (feasible). The conclusion of this research is that the overall material contained in these textbooks are appropriate based on the Learning Objectives (LO) and Learning Achievement (LA) in the Merdeka Curriculum. This book is suitable to be used as a book for schools that have implemented the Merdeka Curriculum. The presentation of the material in these textbooks are in accordance with the description of the substance of the material between sub-chapters which is explained proportionally taking into account Learning Achievements and Learning Objectives.